Influence of Financial Management Accountability and The Spirituality of Pastoral Services In the Parishes of The Tomohon Victory Towards The Achievement of Pastoral Work - Makalew, Maritje Maria; Pangemanan, Stefhanus Hanny (Dinasti Publisher, 2025)
The Manado Diocese Catholic Church implements a Church financial management system within the framework of transparent, objective and responsible financial management. In this context, it is necessary to involve lay pastoral staff who are considered capable and competent and have a high spirituality of service in order to realize the pastoral works of the Manado Diocese Church. This research aims to examine the phenomenon of the influence of accountability in parish financial management and the spirituality of pastoral servants in the context of achieving pastoral work. This research was conducted in all churches or parishes in the Kevikepan Tomohon area by taking 95 samples from 133 populations. The research method used is a quantitative research method with a survey approach. Through this method, researchers want to test hypotheses and at the same time explain the relationship between variables. The data analysis process uses the application of correlation statistics and multiple regression test to analyze the influence between variables and measure the level of relationship between each variable studied. The research results show that: First, there is a significant and linear influence between Financial Management Accountability and Pastoral Work Achievement, meaning that if Financial Management Accountability is implemented well and appropriately it will increase Pastoral Work Achievement in the Tomohon Kevikepan Parishes. Second, there is a relationship between the Spirituality of Pastoral Servants and the Achievement of Pastoral Work. This means that if the Spirituality of Pastoral Servants is interpreted well and effectively, then this will have the effect of increasing the Achievement of Pastoral Work in Tomohon Kevikepan Parishes. Third, the results of hypothesis testing and multiple correlation and multiple regression analysis prove that there is an influence between Financial Management Accountability and Pastoral Servant Spirituality together on Pastoral Work Achievement. Furthermore, it can be concluded that an accountable financial management model supported by the spirituality of pastoral servants can increase the achievement of pastoral work in parishes.